Microstructural behaviour of hot deformed AA 6015 alloy. (4th August 2014) - Evangelista, E .; Forcellese, A.; Gabrielli, F .; Mengucci, P.
The hot workability of AA 6015 alloy has been studied by means of torsion tests over the temperature range 300–500°C and strain rate of 0.1 s −1 . The ductility was very low at 300–350°C but attained large values at higher temperatures. Optical microscopy showed original grains partially elongated up to 350°C and recrystallized grains at higher temperatures. Electron metallography revealed a distribution of fine Mg2 Si precipitates with unrecovered structures at lower temperatures and well defined subgrain with the presence of large Mg2 Si particles at temperatures higher than 400°C. The effect of precipitate size on dynamic restoration was analysed.